Contribution of Vocabulary Knowledge to Reading Comprehension Among Chinese Students: A Meta-Analysis - Dong, Yang; Tang, Yi; Chow, Bonnie Wing-Yin; Wang, Weisha; Dong, Wei-Yang (Frontiers in Psychology, 2020)
This study investigated the correlation between vocabulary knowledge and reading comprehension. To address the correlation picture under Chinese logographical scripts, the researchers investigated the potential explanation for the correlation via the Reading Stage, Information Gap, Content-based Approach, Independent Hypothesis, and Cognition and Creativity Theory approaches. This study undertook a meta-analysis to synthesize 89 independent samples from the primary school stage to the Master degree stage. Results showed the correlation picture as an inverted U-shape, supporting the Independent Hypothesis of the impact of vocabulary knowledge on reading comprehension. In each education stage, the correlation between vocabulary knowledge and reading comprehension was independent in that it did not interact with any significant moderators. This study implicated that the determining factors on reading comprehension were not only decoding and linguistic comprehension; vocabulary knowledge should be the third one.